DISPLACEMENT EFFECTS OF LATVIAN RURAL DEVELOPMENT PROGRAMME 2007-2013 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Periodic evaluation of EU Member States Rural Development Programme (RDP) specific policy interventions is considered crucial in policy development. The main reasons for the evaluation of specific policy interventions are the assessment of a programme’s impact, the improvement of programme management and administration, identification of necessary improvements in the delivery of interventions and meeting the accountability. The core question to be answered in programme evaluation is whether the stated objectives are accomplished by particular intervention (support or „treatment” provided to programme participants). The main problem in the process of evaluation is the assessment of the counterfactual outcome by modelling the situation where treatment is absent. The counterfactual outcome has to be estimated by statistical methods as it is usually not observed. General equilibrium effects occur when a programme affects units other than its participants. The most important possible impacts are the substitution effect and the displacement effect. Displacement effects are unplanned and indirect. They usually play a more important role in the evaluation at the programme level than in the evaluation of RDP individual measures. Displacement effect is the programme effect that occurs in a programme area at expense of another area. It takes place if farms located in one geographical area, which is not a subject to RD support, becomes adversely affected by a support provided to farms located in another geographically area. The existing study provides an assessment of the displacement effects on the employment in unsupported units at the programme level after the net effects on the employment calculated at the measure level are aggregated over the entire programme.